Multiple sensorial media advances and applications new developments in MulSeMedia - Ghinea, George; Andres, Frederic; Gulliver, Stephen R. (Premier reference source, 2012)
"This book provides a comprehensive compilation of knowledge covering state-of-the-art developments and research, as well as current innovative activities in Multiple Sensorial Media and its importance in media design" - Provided by publisher